Peningkatkan Kemampuan Bahasa Anak Dengan Penerapan Metode Pemberian Tugas Berbantuan Media Kartu Huruf di Kelompok B Taman Kanak-Kanak Al Mushlihun Sei Beduk Tahun Ajaran 2021/2022 - Eri Yanti; Darmanina Lisanti; Endang Sulastri (Jurnal Pendidikan Tuntas, 2023)
This research is motivated by facts in the field which show that children's language skills in recognizing letters in Al Mushlihun Kindergarten are still lacking, there are still many children who are not correct when pronouncing letters, this research aims to improve the ability to recognize letters using letter cards in group B at Al Mushlihun Kindergarten. In detail, the ability to be improved is being able to recognize letters, pronounce letters correctly and complete letters to form words. The type of research carried out is Classroom Action Research (PTK) with two learning cycles. Research activities were carried out at Al Mushlihun Kindergarten on group B children, totaling 16 children consisting of 7 boys and 9 girls, and children who were not yet able to recognize letters consisting of 8 children (50%) who did not know letters, 5 children (32%) are starting to recognize letters, 2 children (13%) can already recognize letters, 1 child (5%) can recognize letters well. After carrying out learning improvement activities, improving children's ability to recognize letters using letter card media was able to show development, this can be seen from the data collected in cycle 1, including 3 out of 16 (19%) children who were able to recognize letters, then learning improvements were carried out in activities to recognize letters using letter card media in cycle 2. The data shown consists of 15 children (94%) being able to recognize letters well. So the description of the data collected is that the use of letter card media can improve children's ability to recognize letters in Kindergarten. Kanak Al Mushlihun group B. Key words: language development, letter card media, assignment method.